Distributed simulation of large-scale and detailed models. (22nd September 2009) - D'Angelo, G.; Bracuto, M.
We present a new approach for the distributed simulation of large-scale and detailed models. Our approach increases the simulator speed jointly addressing two main problems of distributed simulation: the reduction of the communication overhead and the load-balancing in the execution cluster. The proposed method dynamically reconfigures the simulation, considering the performance of each part of the execution architecture. In this way, commercial-off-the-shelf hardware can be used for fast and cost-effective simulations. The performance evaluation, based on the 802.11 DCF protocol, demonstrates that this approach is feasible for the detailed simulation of very large-scale models such as wireless networks.